Adaptive Leadership, Employee Recognition and Employee Engagement as Mediator to Employee’s Agility: The Point of View from Supervisors Level Up to Manager - Aji Surya Wicaksono, Gregorius; Maharani, Anita; Pintor Siolemba Patiro, Shine (Jurnal Manajemen (Edisi Elektronik), 2024)
There are three aims of this research: to determine the role of employee recognition on employee agility, the role of adaptive leadership on employee agility, and the role of employee engagement as a mediator between adaptive leadership and employee recognition on employee agility from supervisor’s level up to manager in a manufacturing company focuses in automotive in Jakarta. This research is based on a comprehensive review of existing literature on adaptive leadership, employee recognition, engagement, and agility. The research approach applied in this study is quantitative, using a Partial Least Square Structural Equation Modelling analysis approach. The data for this research was collected through purposive sampling, with the object of this research being one of the subsidiary companies that has implemented the employee agility approach. The findings of this research indicate that adaptive leadership does not have a significant positive influence on employee agility, nor does employee recognition. Additionally, employee engagement was found not to mediate the influence of employee recognition on employee agility.